2019
DOI: 10.5433/1679-0359.2019v40n6supl3p3577
|View full text |Cite
|
Sign up to set email alerts
|

Soybean hulls as feed substitute of ground corn can increase the fiber digestibility and bacterial fibrolytic profile of grazing Nellore steers during the rainy season

Abstract: Soybean hulls as feed substitute of ground corn can increase the fiber digestibility and bacterial fibrolytic profile of grazing Nellore steers during the rainy season Casca de soja como substituto do milho moído pode aumentar a digestibilidade da fibra e o perfil fibrolítico bacteriano de novilhos Nelore em pastejo durante a estação chuvosa AbstractThis study aimed to evaluate the effect of replacement of ground corn by soybean hulls associated or not to whole soybean grain in the feed supplement on intake, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The greater amount of the NPN fraction added to the lesser amount of A + B1 of the carbohydrate fraction caused by the inclusion of soybean hulls means that the rumen pH does not decrease abruptly (Table 3), thus maintaining a rumen environment that favors the growth of fibrolytic bacteria, resulting in greater NDF degradability (Table 4) and confirming earlier reports [22].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The greater amount of the NPN fraction added to the lesser amount of A + B1 of the carbohydrate fraction caused by the inclusion of soybean hulls means that the rumen pH does not decrease abruptly (Table 3), thus maintaining a rumen environment that favors the growth of fibrolytic bacteria, resulting in greater NDF degradability (Table 4) and confirming earlier reports [22].…”
Section: Discussionsupporting
confidence: 87%
“…The inclusion of soybean hulls caused an increase in fraction C, but the lignin in these soybean hulls had characteristics of lower complexation with cellulose and thus these interactions can cause a greater amount of degraded cellulose. This can be seen in Table 4, where the addition of the soybean hulls caused a reduction in fraction I in the DM and CP as well as a reduction of INDF [22].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The soybean hulls present a low lignin content and large proportion of potentially digestible fiber, being very used as primary ingredient in ruminant diets. Many studies have demonstrated the advantages of using soybean hulls as an energy source for ruminants in replacement of corn, as long as it is supplied together with effective fiber sources to reduce the rate of passage and enable ruminant fermentation (Bastos et al, 2015;José Neto et al, 2017;José Neto et al, 2019). Replaces the corn of the ruminant diet with soybean hulls, without changing the quality of animal performance, requires an order of 75%, better digestibility and energy value of the diet, maintaining in certain occasions the economic viability (Alcalde et al, 2009;Gentil et al, 2011).…”
Section: Introductionmentioning
confidence: 99%